Kondisi Keuangan Pemerintah Provinsi Jawa Tengah - Ferica C Putri (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
Since the implementation of the accrual-based government accounting system, accountability in the form of accountability and transparency on financial performance has become something that every government in Indonesia continues to strive for. Local Government Financial Reports (LKPD) as a form of accountability and transparency do not yet contain informative financial reports for all users of financial information. The purpose of this study is to interpret the LKPD of the Central Java Provincial Government from 2018-2020 using three dimensions of financial performance consisting of: 1) Short-Term Solvency, 2) Financial Independence and 3) Financial Flexibility. This research is a descriptive quantitative study with secondary data sources derived from the Budget Realization Report (LRA) of the Central Java Provincial Government. This research is a descriptive analysis based on secondary data processing sourced from the 2018-2020 Central Java Provincial Government Budget Realization Report. The results of research on Short-Term Solvency consisting of Cash Ratios, Quick Ratios and Current Ratios show that the government has the ability to meet its short-term obligations within twelve months, the Financial Independence Ratio shows that the value of independence is low so that the Central Java Provincial government needs to optimize new funding sources from regions, and the Flexibility Ratio shows a decreasing trend every year, which means that the level of financial flexibility to carry out operational activities is relatively low. Keywords: Short-Term Solvency, Financial Independence, Financial Flexibility